EVALUATION OF UTERINE MICROCIRCULATION AS A KEY FACTOR IN THE PATHOGENESIS OF REPRODUCTIVE LOSS (World Bulletin of Social Sciences, 2025)
eproductive losses remain one of the most complex and multidisciplinary problems in modern obstetrics. Despite numerous established etiological factors, a key pathogenetic link is often the disruption of utero-placental blood flow, which is based on disorders at the microcirculatory level. Early diagnosis of these conditions is crucial for preventing pregnancy loss.
Keywords: Reproductive loss; Reproductive lossmicrocirculation